Relationship between CED Status, Pregnant Women and LBW with Stunting Incidence in Toddlers at Dolodou Health Center, West Dumoga District - Millennia Mokoginta; Widia Shofa Ilmiah; Anik Sri Purwanti (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Stunting is a medical condition that significantly affects children's growth and development, resulting in long-term impacts on physical health, cognitive abilities, and productivity in adulthood. The problem often begins during pregnancy and early life, when nutrition and health care play a critical role in determining a child's developmental trajectory. This study aimed to analyze the relationship between the prevalence of stunting among toddlers in the operational area of the Dolodou Health Center UPTD and two key maternal and perinatal factors: chronic energy deficiency (CED) in pregnant mothers and low birth weight (LBW). A cross-sectional design was applied using a quantitative research approach. The study population consisted of all mothers with toddlers in the Dolodou Health Center area, and 31 respondents were recruited using a total sampling technique. Data were collected using structured questionnaires to gather information on maternal nutrition history, pregnancy conditions, and child anthropometric measurements. Chi-square statistical analysis was used to examine the relationships between variables. The results revealed a significant association between stunting and maternal CED status (p = 0.024), indicating that children born to mothers with chronic energy deficiency were at a higher risk of experiencing stunting. Additionally, children with a history of LBW were found to be more likely to suffer from stunting compared to those with normal birth weight. These findings underscore the importance of preventive measures during pregnancy, including nutritional monitoring, dietary supplementation, and health education to prevent both CED and LBW. In conclusion, addressing maternal nutritional health before and during pregnancy, along with continuous monitoring of child growth, is crucial to reducing stunting prevalence. Collaborative efforts between health workers, families, and the community are essential to ensure adequate nutrition and promote healthy development in children.